2015
DOI: 10.4103/0974-8237.167881
|View full text |Cite
|
Sign up to set email alerts
|

Enduring improvement in Oswestry Disability Index outcomes following lumbar microscopic interlaminar decompression: An appraisal of prospectively collected patient outcomes

Abstract: Objectives:Our present study aims to assess the short and long-term postoperative outcome of microscopic interlaminar decompression from a neurosurgical center in a developing country and also aims to further determine any predictors of functional outcome.Materials and Methods:All patients with moderate to severe symptomatic stenosis undergoing elective posterior lumbar spinal decompression were prospectively enrolled in a database. Preoperative, 2 weeks and 2 years postoperative Oswestry Disability Index (ODI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…As such, it is not directly comparable to the individual PROMs utilized in our study. In a study of 60 patients undergoing LD by Khan et al,31 they reported an overall MCID achievement rate for ODI of 83.3% at 2 years’ follow-up which is comparable to our rate of 72.4%–74.5% across subgroups.…”
Section: Discussionsupporting
confidence: 86%
“…As such, it is not directly comparable to the individual PROMs utilized in our study. In a study of 60 patients undergoing LD by Khan et al,31 they reported an overall MCID achievement rate for ODI of 83.3% at 2 years’ follow-up which is comparable to our rate of 72.4%–74.5% across subgroups.…”
Section: Discussionsupporting
confidence: 86%